Short-Chain Alcohols Upregulate GILZ Gene Expression and Attenuate LPS-Induced Septic Immune Response - Ng, Hang Pong; Wang, Yubo; Jennings, Scott; Nelson, Steve; Wang, Guoshun (Frontiers in Immunology, 2020)
Alcohol differentially affects human health, depending on the pattern of exposure. Moderate intake provides beneficial mood modulation and an anti-inflammatory effect, while excessive consumption leads to immunosuppression and various alcohol use disorders. The mechanism underlying this bi-phasic action mode of alcohol has not been clearly defined. Our previous publication demonstrated that ethanol, in the absence of glucocorticoids (GCs), induces expression of Glucocorticoid-Induced Leucine Zipper (GILZ), a key molecule that transduces GC anti-inflammatory effect through a non-canonical activation of glucocorticoid receptor (1). Here we report that similar short-chain alcohols, such as ethanol, propanol and isopropanol, share the same property of upregulating GILZ gene expression, and blunt cell inflammatory response in vitro. When mice were exposed to these alcohols, GILZ gene expression in immune cells was augmented in a dose-dependent manner. Monocytes and neutrophils were most affected. The short-chain alcohols suppressed host inflammatory response to lipopolysaccharide (LPS) and significantly reduced LPS-induced mortality. Intriguingly, propanol and isopropanol displayed more potent protection than ethanol at the same dose. Inhibition of ethanol metabolism enhanced the ethanol protective effect, suggesting that it is ethanol, not its derivatives or metabolites, that induces immune suppression. Taken together, short-chain alcohols per se upregulate GILZ gene expression and provide immune protection against LPS toxicity, suggesting a potential measure to counter LPS septic shock in a resource limited situation.